ANALISIS PENGARUH PENGGUNAAN MEDIA BARU TERHADAP POLA INTERAKSI SOSIAL ANAK DI KABUPATEN SUKOHARJO - Efendi, Agus; Astuti, Puwani Indri; Rahayu, Nuryani Tri (Universitas Muhammadiyah Surakarta, 2017)
This study aims at analyzing and describing the use of digital media by elementary school students, the pattern of social interaction of the students and the influence of new media use on the studentsâ social ability. This research is explanative and has causal correlation with survey method using main instrument of questionnaire. The population covers students aged 8-12 years of elementary school students of Sukoharjo regency with total number 11.263 children fromn 554 elementary schools. The sample size is 80 students. The results showed that the rate of use of new media among the children was in the medium category (1.89), and social interaction in high category (2.45). The assumption which states that the higher the use of new media the social interaction of children tends to be lower is acceptable. It was proved with a correlation coefficient of 0.54 at degrees of freedom 0.05 or 95% confidence level.